Bile Acids as Metabolic Regulators and Nutrient Sensors - Chiang, John Y. L. (Annu Rev Nutr, 2019)
Bile acids facilitate nutrient absorption and are endogenous ligands for nuclear receptors that regulate lipid and energy metabolism. The brain–gut–liver axis plays an essential role in maintaining overall glucose, bile acid, and immune homeostasis. Fasting and feeding transitions alter nutrient content in the gut, which influences bile acid composition and pool size. In turn, bile acid signaling controls lipid and glucose use and protection against inflammation. Altered bile acid metabolism resulting from gene mutations, high-fat diets, alcohol, or circadian disruption can contribute to cholestatic and inflammatory diseases, diabetes, and obesity. Bile acids and their derivatives are valuable therapeutic agents for treating these inflammatory metabolic diseases.